Catalysts of alkaline nitrates supported on oxides for the diesel soot combustion: Deactivation by hydro-treatment and CO2 - Ruiz, Maria Lucia (2013)
The deactivation of supported catalysts CsNO3 and LiNO3 for diesel soot combustion is studied in this work. The effect of hydro-treatment at high temperature and presence of CO2 in feed flow were investigated. Catalysts were characterized by means of X ray diffraction, DSC technique and FTIR. A fixed bed reactor was used to measure activity of fresh and deactivated catalysts with NO2/O2 feed. Thermogravimetrical system with air/CO2 feed was used to study the deactivation with CO2. Catalysts with LiNO3 were the most resistant to deactivation by hydro-treatment, and they are not deactivated by CO2. It is postulated that the cesium nitrate solubilizes in water and is eliminated during the hydro-treatment, instead, lithium species interacted more strongly with the support and generate more resistance species.